Unusual genetic variants associated with hypercholesterolemia in Argentina - Corral, Pablo; Geller, Andrew S.; Polisecki, Eliana Y.; Lopez, Graciela I.; Bañares, Virginia G.; Cacciagiu, Leonardo; Berg, Gabriela; Hegele, Robert A.; Schaefer, Ernst J.; Schreier, Laura E. (Atherosclerosis, 2018)
Marked hypercholesterolemia, defined as low density lipoprotein cholesterol (LDL-C) levels ≥ 190 mg/dL, may be due to LDLR, APOB, and PCSK9 variants. In a recent analysis, only 1.7% of cases had such variants. Our goal was to identify other potential genetic causes of hypercholesterolemia. In a total of 51,253 subjects with lipid testing, 3.8% had elevated total cholesterol >300 mg/dL and/or LDL-C≥190 mg/dL. Of these, 246 were further studied, and 69 without kidney, liver, or thyroid disease and who met Dutch Lipid Clinic Network criteria of ≥6 points had DNA sequencing done at the LDLR, APOB, PCSK9, APOE, LDLRAP1, STAP1, ABCG5, ABCG8, CYP27A1, LIPA, LIPC, LIPG, LPL, and SCARB1 gene loci and also had 10 SNP analysis for a weighted high LDL-C genetic risk score. In the 69 subjects with genetic analyses, the following variants were observed in 37 subjects (53.6%): LDLR (n = 20, 2 novel), ABCG5/8 (n = 7, 2 novel), APOB (n = 3, 1 novel), CYP27A1 (n = 3, 1 novel), LIPA (n = 2, 1 novel), APOE (n = 2), LIPC (n = 1, novel), LIPG (n = 1, novel), and SCARB1 (n = 1); 14 subjects (20.3%) had a high polygenic score, with 4 (5.8%) having no variants. Our data indicate that in addition to variants in LDLR, APOB, PCSK9, APOE, LDLRAP1, and STAP1, variants in ABCG5/8, CYP27A1, LIPA, LIPC, and LIPG may be associated with hypercholesterolemia and such information should be used to optimize therapy. •First data estimating the prevalence of familial hypercholesterolemia (FH) in patients with phenotypic FH in Argentina.•An extended genetic panel was analyzed in index cases with DLCN score ≥6.•33.3% of the mutations were found in traditional genes (LDLR and APOB).•29% of the variants were identified in other genes related to lipoprotein metabolism disorders and/or polygenic causes.•Other unusual sources of FH are highlighted, such as mutations in ABCG5/8 or CYP27A1.